Travessias "no Social": política, cidadania e disputas no Universo Jovem do Lagamar - Avelar, Juliana Nogueira (2012)
The types of action of young residents from a place known as Lagamar will be analyzed in this paper in order to understand the "social work" and arguments that support this kind of activity. Taking as starting point the members of three local organizations that were taken into consideration the lessons learned and experienced the projects to which the young actors joined during their careers. The objectives of the organizations studied take in consideration the overcoming of different social issues. The meanings around the youth concept as well as understandings of the politics are presented in this work as key elements for the analysis of performance "inside the society." From an ethnographic perspective, systematic visits were made in the field in which informal conversations, interviews, participation in activities sponsored by organizations and young people living with resulted in the material that led the proposed analysis. Related to the Involvement of young people surveyed, in a community-oriented projects, there are triggered memories, projects, constructions of meaning and disputes that enable us to have an interesting analysis of politics in everyday living.